2022
DOI: 10.1108/mrr-01-2021-0043
|View full text |Cite
|
Sign up to set email alerts
|

Definitions and antecedents of engagement: a systematic literature review

Abstract: Purpose The purpose of this study is to present a systematic literature review in the research area of engagement focusing on employee and work engagement. In this respect, this study aims to focus on the definitions between employee and work engagement and their differences, as well as to identify the antecedents of the relevant body of knowledge on engagement. Design/methodology/approach A systematic literature review was conducted drawing on an evidence base of 110 articles published in three- and 4-rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 91 publications
2
28
0
3
Order By: Relevance
“…Job resources refer to the physical, psychological and organizational aspects of the work that reduce job demands and help achieve work goals (Bakker and Demerouti, 2008). For example, job characteristics (Rana et al, 2014;Saks, 2019), job control, job fit (Wollard and Shuck, 2011), supervisory support, colleague support, feedback and autonomy are among the most commonly assessed job resources that drive employee engagement (Bailey et al, 2015;Saks, 2006;Kossyva et al, 2022;Lee et al, 2017). Other studies found a positive relationship between leadership and employee engagement (Carasco-Saul et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Job resources refer to the physical, psychological and organizational aspects of the work that reduce job demands and help achieve work goals (Bakker and Demerouti, 2008). For example, job characteristics (Rana et al, 2014;Saks, 2019), job control, job fit (Wollard and Shuck, 2011), supervisory support, colleague support, feedback and autonomy are among the most commonly assessed job resources that drive employee engagement (Bailey et al, 2015;Saks, 2006;Kossyva et al, 2022;Lee et al, 2017). Other studies found a positive relationship between leadership and employee engagement (Carasco-Saul et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the organizational level, research shows that factors such as HRD positively influence employee engagement. For example, HRD practices that can boost employee engagement include opportunities for training and development (Lee et al , 2017), talent management (Wollard and Shuck, 2011), rewards and recognition (Basbous and Malkawi, 2017; Kossyva et al , 2022), coaching (Lyons and Bandura, 2021) and performance management (Alam et al , 2022). Also, existing literature supported other factors such as a climate of psychological safety (Bailey et al , 2015), team and coworkers support (Lee et al , 2017) and connection to mission and values (Akingbola and van den Berg, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The nine-item self-report Utrecht Work Engagement Scale (UWES), which was developed by Schaufeli and Bakker (2004), was used to measure Work Engagement. UWES is the most used measurement instrument to assess the construct of engagement (Kossyva et al, 2022) and it is also adopted in Greek, having a high degree of internal consistency. This constituted a short version of a more detailed one that consisted of seventeen items in a seven-point scale (from 0 5 Never, to 6 5 Always).…”
Section: Methodsmentioning
confidence: 99%
“…Our study draws on both conservation of resources (COR) theory (Hobfoll, 2001) and job demands–resources (JD-R) theory (Demerouti et al , 2001), which constitute the most common theories in the research area of engagement (Kossyva et al , 2022).…”
Section: Introductionmentioning
confidence: 99%